Correlation between Clinical Parameters with Ovarian Endometriosis Cysts: Three-Year Cases at a Tertiary Hospital, Indonesia - Nabilah Mukti Rifahmi; Willy Sandhika; Gadis Meinar Sari; Shaun Ashley Chin (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Endometriosis is a common gynecological problem, globally around 10% (190 million) of women's reproductive age. Several factors increase the risk of endometriosis, including patient's age, length of menstrual cycle, age of giving birth to first child, number of parity, breastfeeding, use of hormonal contraception, flour albus, body mass index (BMI), and caffeine consumption. This study aims to determine the difference and the correlation of risk factors between endometriosis cysts and nonendometriosis cysts. Methods: This research was a cross-sectional study. The subjects of total 194 patients were chosen by consecutive sampling. This research used medical record methods and interviews. The findings were analyzed using univariate methods and binary logistic regression. Results: Clinical parameters such as patient's age, hormonal contraception, frequency of recurrence flour albus, breastfeeding, BMI, and caffeine consumption had no significant correlation with endometriosis cysts case. Meanwhile, the number of parity, age of giving birth to first child, length of menstrual cycle, and characteristics of flour albus have a significant correlation with endometriosis cysts. Conclusions: There are correlation between clinical parameters as a number of parity, age of giving birth to first child, length of the menstrual cycle, and characteristics of flour albus with ovarian endometriosis cyst. Screening risk factors such as nulliparous, flour albus, giving birth for the first time at >30 years, and having a long menstrual cycle could prevent late diagnostic of endometriosis.